Did Ptolemy make novel predictions? Launching Ptolemaic astronomy into the scientific realism debate - Carman, Christian Carlos (2015)
The goal of this paper, both historical and philosophical, is to launch a new case into the scientific realism debate: geocentric astronomy. Scientific realism about unobservables claims that the non-observational content of our successful/justified empirical theories is true, or approximately true. The argument that is currently considered the best in favor of scientific realism is the No Miracles Argument: the predictive success of a theory that makes (novel) observational predictions while making use of non-observational content would be inexplicable unless such non-observational content approximately corresponds to the world "out there". Laudan's pessimistic meta-induction challenged this argument, and realists reacted by moving to a "selective" version of realism: the approximately true part of the theory is not its full non-observational content but only the part of it that is responsible for the novel, successful observational predictions. Selective scientific realism has been tested against some of the theories in Laudan's list, but the first member of this list, geocentric astronomy, has been traditionally ignored. Our goal here is to defend that Ptolemy's Geocentrism deserves attention and poses a prima facie strong case against selective realism, since it made several successful, novel predictions based on theoretical hypotheses that do not seem to be retained, not even approximately, by posterior theories. Here, though, we confine our work just to the detailed reconstruction of what we take to be the main novel, successful Ptolemaic predictions, leaving the full analysis and assessment of their significance for the realist thesis to future works.